Experience With Opportunistic Salpingectomy in a Large, Community-Based Health System in the United States. Issue 2 (August 2016) - Garcia, Christine; Martin, Maria; Tucker, Lue-Yen; Lyon, Liisa; Armstrong, Mary Anne; McBride-Allen, Sally; Littell, Ramey D.; Alabaster, Amy; Raine-Bennett, Tina; Powell, C. Bethan
Abstract : OBJECTIVE: To evaluate the trend in uptake of salpingectomy at the time of hysterectomy and assess physicians' attitudes toward the practice. METHODS: This was a retrospective cohort study using the electronic medical record to identify women 18 years of age or older undergoing hysterectomy from June 2011 to May 2014 in a large integrated health care delivery system. The primary outcome was the change in rate of opportunistic salpingectomy over time and after a systemwide practice recommendation was issued in May 2013. Secondary outcomes included data on blood loss, operating time, and length of stay. RESULTS: Of the 12, 143 hysterectomies performed over the 3-year study period, 7, 498 were performed without oophorectomy. There was a statistically significant rise in rate of salpingectomy over time from 14.7% for June 2011 to May 2012 to 44.6% from June 2012 to May 2013 and to 72.7% from June 2013 to May 2014 ( P <.001). Sixty-one percent of laparoscopic hysterectomies were performed with salpingectomy, whereas only 25% of abdominal and 17% of vaginal hysterectomies had salpingectomies. Median estimated blood loss was lower in the salpingectomy group, 100 compared with 150 mL ( P <.01). There was a significantly shorter median operating time (147 compared with 154 minutes, P =.002) for laparoscopic hysterectomy with bilateral salpingectomy compared with laparoscopic hysterectomy alone. CONCLUSION: Rates of salpingectomy increased significantly over time, consistent with the high reported acceptance rate reported by health care providers and highlighting the importance of physician education to improve compliance with risk-reducing clinical strategies. Abstract : Supplemental Digital Content is Available in the Text.Incorporation of opportunistic salpingectomy significantly increased after an educational intervention with no clinically significant differences seen for blood loss or operating time.